PENGARUH MEKANISME CORPORATE GOVERNANCE, REPUTASI KAP, DEBT DEFAULT DAN FINANCIAL DISTRESS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Brilina Elita Mada; Herry Laksito (Diponegoro Journal of Accounting, 2013)
This research aimed to show empirical proves about the effect of corporate governance mechanism, KAP reputation, debt default, and financial distress to an acceptance of going concern audit opinion. Hypothesis proposed by the researcher were (1) Concentrated ownership affected the acceptance of going concern audit opinion, (2) Managerial ownership affected the acceptance of going concern audit opinion, (3) Independent commissionaire affected the acceptance of going concern audit opinion, (4) KAP reputation affected the acceptance of going concern audit opinion, (5) Debt default affected the acceptance of going concern audit opinion, (6) Financial distress affected the acceptance of going concern audit opinion. The sample of this research was manufacturing firm in the period of 2010-2011. Purposive sampling technique was used to obtain the sample. Logistic regression was used to analyze the data. The variables of this research were centralized ownership, managerial ownership, independent commissionaire, debt default, KAP reputation, and financial distress.The result shows that centralized ownership, debt default, and financial distress have significant effect on the acceptance of going concern audit opinion, while managerial ownership, independent commissionaire, and KAP reputation do not have significant effect on the acceptance of going concern audit opinion.